Diseño conceptual de la planta de tratamiento de aguas residuales del casco urbano del municipio de Pesca, Boyacá (2022)
In the present work, the conceptual design proposal of a wastewater treatment plant (WWTP) for the municipality of Pesca Boyacá was presented, initially it was necessary to carry out a physicochemical diagnosis of the wastewater by means of a composite sample, where tests for the determination of parameters such as BOD, COD, total solids and hardness where it was found that the values ​​of BOD and COD were 165 mgO2/L and 339 mgO2/L respectively, later a comparison of the values ​​obtained previously with the found in Resolution 631 of 2015, Resolution 3560 of 2015 and previous studies presented by the mayor of the municipality, where it is evident that each of the parameters obtained in the report do not comply with the regulations, except for the pH that is within the range allowable with a value of 7.2.